Rorschach, We Have a Problem! The Linguistics of First Contact in Watts's Blindsight and Lem's His Master's Voice. - Głaz, Adam (Science Fiction Studies, 2014)
In Peter Watts's Blindsight, a super-intelligent but non-conscious artifact calling itself Rorschach imitates human speech and thus fakes linguistic communication with people. I question the validity of this idea and use Stanis»aw Lem's His Master's Voice as a counter-example. Problems with "Rorschach-as-fake-speaker" are discussed in the light of findings in linguistics, with the overarching argument that Rorschach would need to obtain access to the semantic and symbolic sphere of language for this to be possible. I maintain that a being without consciousness cannot do this.